PENGARUH TATA KELOLA PERUSAHAAN, PERENCANAAN PAJAK, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PT PRASIDHA ANEKA NIAGA TBK PERIODE 2014–2025 - Arif Hidayat; Karolina Karolina (Worksheet : Jurnal Akuntansi, 2026)
This study aims to examine the effect of corporate governance, tax planning, and financial performance on firm value at PT Prasidha Aneka Niaga Tbk for the period 2014–2025. The research method used is a quantitative approach with multiple linear regression analysis using SPSS. Secondary data were used in the form of annual financial reports of the company over 12 years. Corporate governance is proxied by institutional ownership, tax planning by the effective tax rate (ETR), financial performance by return on equity (ROE), and firm value by Tobin's Q. Partial results show that corporate governance has a significant effect on firm value (sig. 0.037 < 0.05; t-count 2.512 > t-table 2.364). Tax planning does not significantly affect firm value (sig. 0.439 > 0.05). Financial performance also does not significantly affect firm value (sig. 0.989 > 0.05). Simultaneously, all three variables have a significant effect on firm value with F-count 4.757 and sig. 0.034 < 0.05.